2009
DOI: 10.1159/000228543
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Extracellular Volume and Blood Pressure in Hemodialysis and Peritoneal Dialysis Patients

Abstract: Background: Extracellular volume (ECV) assessment by bioimpedance analysis is a reliable technique for determining post dialysis target weight. Overhydration and dehydration are two points of dialysis patients’ fluid status and both affect blood pressure. We compared ECV and blood pressure between hemodialysis and peritoneal dialysis patients. Methods: We studied ECV of 74 (38 females and 36 males) normal subjects, 121 (63 females and 58 males) stable chronic hemodialysis and 84 (57 females and 27 males) stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Although none of these studies used PD as a comparison group, it is plausible that some of the known benefits of HHD over facility HD also apply when comparing HHD with PD. Indeed, although PD allows constant ultrafiltration, total fluid removal can sometimes be limited and possibly, lead to hypervolemia and hypertension (44)(45)(46)(47). Comparison of clearance quality between PD and HD is limited, although it seems reasonable to postulate that patients treated with long or long/frequent HHD receive a higher dialysis dose than most patients on PD.…”
Section: Discussionmentioning
confidence: 99%
“…Although none of these studies used PD as a comparison group, it is plausible that some of the known benefits of HHD over facility HD also apply when comparing HHD with PD. Indeed, although PD allows constant ultrafiltration, total fluid removal can sometimes be limited and possibly, lead to hypervolemia and hypertension (44)(45)(46)(47). Comparison of clearance quality between PD and HD is limited, although it seems reasonable to postulate that patients treated with long or long/frequent HHD receive a higher dialysis dose than most patients on PD.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that overhydration and hypertension are more common in PD patients than in HD patients. 25 Thus, in PD patients, serum apelin level can be higher than HD patients because they are more often hypervolemic than HD patients. In a different study performed by Koç et al, they found that LVMI was significantly higher in CAPD patients with uncontrolled hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Bioelectrical impedance (BIA) is a simple and low-cost method that can be useful in clinical practice to estimate the volume overload in HD patients [7,8,9]. However, until the present time, few studies showed parameters for the interpretation of the data provided by BIA associating them with total body water (TBW) or BP control.…”
Section: Introductionmentioning
confidence: 99%